2014
DOI: 10.1080/11250003.2014.940007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of species diversity for sarcosaprophagous Diptera across a pronounced elevational gradient in central Spain

Abstract: Measuring the biological diversity in a given area can provide valuable approaches not only to conserve ecological systems, but also to understand their functioning and organization. The current paper analyzes the species richness and diversity patterns of sarcosaprophagous Diptera across an elevational gradient of natural habitats in central Spain, and the relationship between the species diversity and the environmental variables defining each habitat. The calculation of randomized species richness curves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Most species of the family Calliphoridae have a wide geographical distribution and are habitually associated with human activities. In this regard, measuring their diversity and studying their relationship with the environmental variables at local scales can provide valuable approaches to better understand their functioning and organization, and to better adapt interpretations to the generally highly variable local and environmental conditions [5,31]. However, their relationship with altitudinal gradients has often received little attention, especially in the Mediterranean region [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most species of the family Calliphoridae have a wide geographical distribution and are habitually associated with human activities. In this regard, measuring their diversity and studying their relationship with the environmental variables at local scales can provide valuable approaches to better understand their functioning and organization, and to better adapt interpretations to the generally highly variable local and environmental conditions [5,31]. However, their relationship with altitudinal gradients has often received little attention, especially in the Mediterranean region [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support our hypothesis: altitude influences both the abundance and the altitudinal distribution pattern of calliphorids. We observed a marked decrease in the calliphorid abundance with increasing altitude, a phenomenon that can be explained as a response to changes in temperature, which usually decrease with increasing altitude [31]. Indeed, this is an important environmental factor that determines the abundance of insect species because it influences their activity and their reproductive, nutritional and, in general, physiological success [5, 31, 45–47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have also confirmed the connection between species richness and those two elements. Martín-Vega et al (2016) found that elevation is negatively correlated with species richness in Spain [ 145 ]. It can be assumed that this is connected with the transport of people and goods along the coastline.…”
Section: Discussionmentioning
confidence: 99%